Criminal Law Policy on Terrorism with a Deradicalization Approach toward the Realization of Rehabilitative Justice - Md Shodiq (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Criminal law policy in countering terrorism faces a serious challenge to maintain a balance between the interests of state security and the protection of human rights. An overly repressive approach has the potential to lead to rights violations, while an overly lenient approach can reduce the effectiveness of prevention. Therefore, deradicalization was developed as a non-penal strategy that complements criminal law enforcement. This study aims to analyze the extent to which terrorism criminal law policies that integrate deradicalization approaches reflect the principle of balance between enforcement, prevention, and rehabilitation. This research uses normative legal research methods with legislative, conceptual, and philosophical approaches. Data were obtained through a literature study of current laws and regulations, legal doctrines, and related policy documents, which were analyzed qualitatively through legal reasoning and systematic interpretation. The results of the study show that the policy of terrorism criminal law has undergone a paradigm shift towards an integrative model that combines penal and non-penal instruments, with deradicalization as an important element to prevent recidivism and support social reintegration. In conclusion, the integration of deradicalization within terrorism criminal law policy not only reflects the principle of balance between enforcement, prevention, and rehabilitation, but also constitutes a normative foundation for the realization of rehabilitative justice oriented toward social reintegration and the prevention of recidivism.